Food Food Security of Lift Net Fishermen in Central Tapanuli, North Sumatra: Ketahanan Pangan Rumah Tangga Nelayan Bagan Tancap di Tapanuli Tengah, Sumatera Utara - Tirta Anugerah; Rahmaini Gea; Eddiwan; Husnul Yaqin Harahap; Tika Nisari (Fakultas Ilmu Sosial dan Politik, Universitas Negeri Surabaya, 2026)
Household food security among fishing communities is important to study because this group is vulnerable to income fluctuations and limited economic access. An analysis of socio-economic factors is needed to understand the causes and levels of food security among traditional fishers in coastal areas. Data were collected through a survey of 78 lift-net fishing households. The study shows that most lift-net fishing households in Muara Nibung Village are food insecure. Partially, income significantly affects the level of household food security, while simultaneously, factors such as income, expenditure, family size, and mother's education influence the food security level of fishing households.